Physical activity and sedentary behavior patterns and sociodemographic correlates in 116,982 adults from six South American countries: the South American physical activity and sedentary behavior network (SAPASEN) - André O. Werneck; Se-Sergio Baldew; J. Jaime Miranda; Oscar Díaz Arnesto; Brendon Stubbs; Danilo R. Silva; on the behalf of the South American Physical Activity and Sedentary Behavior Network (SAPASEN) (BMC, 2019)
Abstract Background Physical inactivity and sedentary behavior are major concerns for public health. Although global initiatives have been successful in monitoring physical activity (PA) worldwide, there is no systematic action for the monitoring of correlates of these behaviors, especially in low- and middle-income countries. Here we describe the prevalence and distribution of PA domains and sitting time in population sub-groups of six south American countries. Methods Data from the South American Physical Activity and Sedentary Behavior Network (SAPASEN) were used, which includes representative data from Argentina (n = 26,932), Brazil (n = 52,490), Chile (n = 3719), Ecuador (n = 19,851), Peru (n = 8820), and Suriname (n = 5170). Self-reported leisure time (≥150 min/week), (≥150 min/week), transport (≥10 min/week), and occupational PA total (≥10 min/week), as well as sitting time (≥4 h/day) were captured in each national survey. Sex, age, income, and educational status were exposures. Descriptive statistics and harmonized random effect meta-analyses were conducted. Results The prevalence of PA during leisure (Argentina: 29.2% to Peru: 8.6%), transport (Peru: 69.7% to Ecuador: 8.8%), and occupation (Chile: 60.4 to Brazil 18.3%), and ≥4 h/day of sitting time (Peru: 78.8% to Brazil: 14.8%) differed widely between countries. Moreover, total PA ranged between 60.4% (Brazil) and 82.9% (Chile) among men, and between 49.4% (Ecuador) and 74.9% (Chile) among women. Women (low leisure and occupational PA) and those with a higher educational level (low transportation and occupational PA as well as high sitting time) were less active. Concerning total PA, men, young and middle-aged adults of high educational status (college or more) were, respectively, 47% [OR = 0.53 (95% CI = 0.36-0.78), I2 = 76.6%], 25% [OR = 0.75 (95% CI = 0.61-0.93), I2 = 30.4%] and 32% [OR = 0.68 (95% CI = 0.47-1.00), I2 = 80.3%] less likely to be active. Conclusions PA and sitting time present great ranges and tend to vary across sex and educational status in South American countries. Country-specific exploration of trends and population-specific interventions may be warranted.